Experimental Verification of the Relation between the Surface Roughness and the Type of Used Tool Coating - Kasina, Marek; Vasilko, Karol (Manufacturing Technology Journal, 2012)
This contribution deals with the need of continual experimental study of the phenomenon that relates to the increasing demands to the quality of engineering production and also to the productivity and economy of the production. Experimental part is focused to the influence of the tool coatings, which significantly affect the roughness of the material machined with the use of the cutting plates made of high-speed cutting steel. The plates were used in the series of the experiments, what allows us to create the models of real situations in the area of concrete manufacturing technology and subsequently to analyze them. To the measured and evaluated parameters belonged: the roughness of the machined material after the use of coated and uncoated tools. Planing technology is realized until there are major visible changes in cross roughness of the machined material, what means the increasing of Rz values. This is caused by the fact, that the coating was removed from the cutting edge, what is considered as the blunting of the tool. Measured values are statistically expressed in the form of the graphs.
Keywords: planing; tool coating; roughness; cutting tool; high-speed steel